1997
DOI: 10.3758/bf03210785
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and identifying response-compatible stimuli

Abstract: Previous work indicates that action-control processes influence perceptual processes: The identification probability of a left-or right-pointing arrow is reduced when it appears during the execution of a compatible left-right-key press (Mtisseler& Hommel,in press). The present study addresses the question of whether this effect would also be observed in a detection task-that is, with judgments that do not require discriminating between left-and right-pointing arrows. Indeed, we found comparable effects in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 11 publications
4
88
1
2
Order By: Relevance
“…For instance, the perception of biological motion and the perceived apparent motion of bodies are both influenced by the body's own repertoire of actions (Calvo-Merino, Glaser, Grèzes, Passingham, & Haggard, 2005;Casile & Giese, 2006;Oh & Shiffrar, 2007;Shiffrar & Freyd, 1990); the perception of object features such as orientation and direction is influenced by planned and executed movements (Lindemann & Bekkering, 2009;Müsseler & Hommel, 1997;Zwickel, Grosjean, & Prinz, 2010); eye movements are drawn to objects oriented in the same direction as the planned grasp (Bekkering & Neggers, 2002); and the detection of changes in orientation is enhanced when one is planning to grasp an object (Gutteling, Kenemans, & Neggers, 2011). This body of research has demonstrated many influences of action on perception.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the perception of biological motion and the perceived apparent motion of bodies are both influenced by the body's own repertoire of actions (Calvo-Merino, Glaser, Grèzes, Passingham, & Haggard, 2005;Casile & Giese, 2006;Oh & Shiffrar, 2007;Shiffrar & Freyd, 1990); the perception of object features such as orientation and direction is influenced by planned and executed movements (Lindemann & Bekkering, 2009;Müsseler & Hommel, 1997;Zwickel, Grosjean, & Prinz, 2010); eye movements are drawn to objects oriented in the same direction as the planned grasp (Bekkering & Neggers, 2002); and the detection of changes in orientation is enhanced when one is planning to grasp an object (Gutteling, Kenemans, & Neggers, 2011). This body of research has demonstrated many influences of action on perception.…”
Section: Discussionmentioning
confidence: 99%
“…It also predicts facilitative priming for an action plan that has complete feature code overlap with an action plan currently held in memory (see Hommel et al, 2001;Stoet & Hommel, 1999), because only one action plan would be represented (available for selection), and this plan would be available earlier for activating a response than would a more recently constructed action plan. Finally, this selection account predicts that recognition of a briefly presented perceptual stimulus that shares a feature code (cognitive code) with a planned action currently held in memory would be delayed, leading to more recognition errors, relative to when these two events do not share codes (e.g., see results by Müsseler & Hommel, 1997a, 1997bMüsseler & Wühr, 2002;Wühr & Müsseler, 2001; for a review, see Hommel et al, 2001). This recognition delay would be attributed to a delay in selecting the correct representation corresponding to the relevant stimulus event when the two events share similar codes and are therefore highly confusable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence by Wiediger and Fournier (in press) also shows that motor overlap is not sufficient for CI to occur, particularly when responses are based on stimulus detection, where cognitive demands required for the action event are relatively low and likely do not require the generation of feature codes. These findings suggest that it is not effector or motor overlap, but an overlap in the feature codes (e.g., right or left) that makes up the action plan that causes CI (see also Müsseler & Hommel, 1997a, 1997bMüsseler & Wühr, 2002;Wühr & Müsseler, 2001).…”
Section: Experiments 1a and 1bmentioning
confidence: 99%
“…However, activating codes does not form an action plan; a stage which involves binding feature codes in a manner akin to feature integration theory for object representation (Kahneman & Treisman, 1984). When features are bound into a single event representation -as required for completion of the action plan -the codes are 'occupied', generating attenuated perception of events activating them (Müsseler & Hommel, 1997a;1997b). Given that these mechanisms generating perceptual facilitation followed by attenuation are proposed to operate in order to generate action plans, one might expect that this framework would hypothesize the perceptual shift to occur prior to action execution, and therefore that it could only explain the attenuating influences observed in the present study.…”
Section: Discussionmentioning
confidence: 99%